ENTREPRENEURIAL POTENTIALS OF STUDENTS OF TOURISM AND HOSPITALITY - Jovičić Vuković, Ana Đ.; Papić-Blagojević, Nataša (International Journal of Economic Practice and Policy, 2019)
The paper will explore the perception of students about the concept of entrepreneurship, their willingness to become entrepreneurs and factors that can influence on that. The aim of the research is to analyse and identify the entrepreneurial potential of students of tourism and hospitality study programmes on a sample of 104 students of applied studies. On the basis of the obtained results, it will be concluded how students perceive their own business start-up capacities, the level of external support, and possible restrictions on the launch of entrepreneurial ventures. The results of the research indicate the key problems and difficulties for young entrepreneurs. Insufficient knowledge needed to start their own business venture, insufficient information on existing entrepreneurship support programs, middle level of support that young people receive in higher education are the basic problems that young entrepreneurs face during and after their education. Based on the identified difficulties, it is necessary to provide improvements in terms of institutional support to the development of entrepreneurship, the improvement of the education system, or the development of entrepreneurial potential at all levels and in all forms of education. Also, a higher level of support by educational institutions, but also providing better information on market opportunities and programs of financial and other forms of support are key factors for the development of entrepreneurial potentials of young people.